Patient Safety Climate and Its Affecting Factors Among Rehabilitation Health Care Staff of Hospitals and Rehabilitation Centers in Iran-Tehran - Alireza Khammar; Mohsen Poursadeghiyan; Hossein Marioryad; Reza Nabi Amjad; Monir Alimohammadi; Mohammad Khandan (Iranian Rehabilitation Journal, 2019)
Objectives: Hospitals and clinical centers are concerned about patient safety. Safety climate is a perceived value of safety in an organization that could improve the safety of workers and patients. The present research was conducted to study the safety climate of patients in the hospitals and rehabilitation centers affiliated to the University of Social Welfare and Rehabilitation Sciences. Methods: This descriptive-analytical study was conducted on 300 nurses and nurse’s aides (healthcare staff) who were selected by stratified sampling method, from two hospitals and three clinics, in 2017. Data collection tools included Patient Safety Climate Scale presented by Kudo and a demographic data questionnaire. The obtained data were analyzed by SPSS using descriptive statics like frequencies and percentages. Furthermore, Mann-Whitney U test and Kruskal-Wallis test were used to analyze the obtained data and compare the mean scores, respectively. Results: The Mean±SD age and work experience of study participants were 36.7±6.79 and 9.46±5.8 years, respectively. The patient safety climate sub-factors were significantly different between males and females (P<0.05) except for reporting aspect (P>0.05). Patient safety climate was only different in nursing condition (P=0.013) among studied healthcare centers. Also, only fatigue reduction was different among various studied wards (P=0.035), where intensive care unit had the lowest score (2.12±2.0). Discussion: Overall, the poor condition of patient safety climate was found in the studied rehabilitation centers. Therefore, it is recommended to improve nurses’ attitudes with the assistance of hospital managers, to enhance patient safety.